A Critical Analysis of Social Engineering Theory in the Context of Legal Development in Indonesia - Purnama, Hamdan; Iskandar, Iskandar (CV. Ulil Albab Corp, 2024)
The theory of Social Engineering is a legal theory that views law as a tool for social engineering. However, the concept of Social Engineering in the context of legal development in Indonesia faces gaps in its implementation, often clashing with social, economic, political, and cultural realities. This research aims to analyze the concept of Social Engineering, as proposed by Roscoe Pound, within the framework of modern law. It also seeks to evaluate the relevance of this theory to legal development in Indonesia. This study adopts a normative juridical method with a conceptual approach. The data used is secondary in nature, derived from primary, secondary, and tertiary legal sources. Data collection is conducted through a literature review, while data analysis is performed qualitatively. Roscoe Pound's Social Engineering theory views law as a tool to create a balance of interests within society, aiming to meet its ever-evolving needs. In a modern context, this theory aligns with an approach that considers the impact of legal policies on social welfare. In Indonesia, the application of this theory is evident in legal reforms focused on social justice and public welfare. However, challenges such as weak law enforcement and discrepancies between policies and social realities need to be addressed in order to achieve effective legal development. Keywords: Theory; Law; Social Engineering.